2018
DOI: 10.1101/322131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional connectivity alterations of the temporal lobe and hippocampus in semantic dementia and Alzheimer’s disease

Abstract: Abbreviations: AD = Alzheimer's disease; FC = functional connectivity; HC = healthy controls; ROI = region of interest; SD = semantic dementia AbstractThe severe semantic memory impairments in semantic dementia have been attributed to a pronounced atrophy and functional disruption of the anterior temporal lobes. In contrast, medial and posterior temporal lobe damage is predominantly found in patients with Alzheimer's disease, and has been associated with episodic memory disturbance. Despite these distinct neur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…The anterior hippocampus forms preferential connections to the temporal pole (Kahn et al, 2008) via the uncinate fasciculus (Kier et al, 2004), laying the groundwork for greater functional connectivity at rest (Honey et al, 2009) and during semantic processing (e.g., Hoffman & Morcom, 2018). Indeed, patients with semantic dementia often demonstrate damage and altered intrinsic functional connectivity to both of these regions (e.g., Chan et al, 2001; Schwab et al, 2020). If these regions are recruited to support episodic AM recollection in older adults, such memories might necessarily be “semanticized,” or imbued with more semantic information (Spreng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The anterior hippocampus forms preferential connections to the temporal pole (Kahn et al, 2008) via the uncinate fasciculus (Kier et al, 2004), laying the groundwork for greater functional connectivity at rest (Honey et al, 2009) and during semantic processing (e.g., Hoffman & Morcom, 2018). Indeed, patients with semantic dementia often demonstrate damage and altered intrinsic functional connectivity to both of these regions (e.g., Chan et al, 2001; Schwab et al, 2020). If these regions are recruited to support episodic AM recollection in older adults, such memories might necessarily be “semanticized,” or imbued with more semantic information (Spreng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The profile of effective connectivity alterations in SD extended beyond local temporal lobe circuitry, additionally involving connections beyond the temporal lobe. Involvement of structural and functional connections between orbitofrontal and anterior temporal cortex-in particular, uncinate fasciculus-has been shown to be a structural signature of SD 6,29,44,65 . Functionally, this is now revealed as an abnormally enhanced excitatory communication, originating primarily in left orbitofrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Previous structural and tractographic studies have implicated orbitofrontal and anterior temporal cortices and their connections in the pathogenesis of disinhibition 68 71 . Studies addressing the functional connectivity of the culprit network in SD have reported altered resting-state fronto-temporal connectivity but have not addressed the mechanism of the behavioural phenotype 29 , 51 , 65 . Our findings argue for a mechanism that is at least partly in common with the pathophysiology of semantic impairment; the effective connectivity profile of social disinhibition implicating a conjunction of intrinsically degraded social conceptual representations and tonically overactive top-down control.…”
Section: Discussionmentioning
confidence: 99%
“…An AD disease progression timeline analysis found that the superior temporal gyrus anterior division was among the top biomarkers to first become abnormal (Venkatraghavan et al, 2019). Functional connectivity analysis found decreased connectivity in the superior temporal gyrus in dementia patients including AD (Hafkemeijer et al, 2015; Schwab et al, 2018). The middle temporal gyrus has been shown to atrophy significantly in both MCI and AD patients when compared to controls in longitudinal studies (Ghazi et al, 2019) and research that combined multi-modal data types (Convit et al, 2000; Korolev et al, 2016).…”
Section: Discussionmentioning
confidence: 99%